Determinants of vegetable and fruit consumption in Colombia (2017)
This study aim to identify the determinants of consumption of vegetables and fruits in an application for Colombia. In order to do this, two types of specifications are used: in the first, a Tobit Model is used to estimate the determinants of household consumption expenditures. Then, a logistic regression model calculates the probability of consumption of this type of foods. The data used come from the national survey of income and expenditure of DANE in the period 2006-2007. The results show that the income, the socio-economics stratus and the size of the households as well as the type of employment and the sex of the individuals are fundamental factors in the consumption of vegetables and fruits. On the other hand, against what was expected education do not seem statistically consistent to these two specifications, the results show that this variable helps to increase spending but decreases the probability of consumption.